EVALUATION OF AUTOCHTHONOUS PRIMARY PRODUCTIVITY OF THE LANOSO STREAM (EPA OF UBERABA RIVER), MINAS GERAIS, BRAZIL - Pedro de Souza Lopes Silva; Vinícius Silva Rodrigues; Fernanda Rezende Terra; Caroline Fávaro Oliveira; Helen Sandra de Sousa Laet; Afonso Pelli (UNINGÁ Review, 2019)
The evaluation of the primary productivity in lotic environments has great relevance, since it allows to know the metabolism of aquaticsystem,as well as the entrance of energy and the influences in the cycles of carbon and other variables. In the water bodies, the abiotic conditions have undergone alterations due to the anthropic interferences, causingimpacts in aquatic communities. The study was carried in Córrego Lanoso, in city of Uberaba/MG. With the objective of evaluating the primary productivity of a lotic environment and analyzing the influence of water quality parameters, sampling was performed to determinethe primary productivity. This was done in two distinct points of Lanoso Stream;the methodology used was method of light and dark bottles by means of the technique of Winkler, modified by Pomeroy and Kirschmann, 1945. The physical-chemical parameters (temperature, turbidity and pH) were obtained in situ via probe. The results showed that the primary productivity was higher at the point near nascent, when compared to the downstream. Regarding the physical-chemical parameters, only turbidity obtained a significant variation, being thislimiting factor for theprimary productivity, since greater turbidityless absorption of light and henceless phytoplanktonic activity of ecosystem